การวิเคราะห์องค์ประกอบเชิงยืนยันการใช้เทคโนโลยีสารสนเทศเพื่อการเรียนรู้ ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 - พาผล(Yossawat Phaphol), ยศวัฒน์; ลังกา(Wilailak Langka), วิไลลักษณ์; เซ็มเฮง(Suwaporn Semheng), สุวพร; เจริญสุข(Onuma charoensuk), อรอุมา (Journal of Behavioral Science for Development, 2016)
(A Confirmatory Factor Analysis of Information and Communication Technology Using for Learning of Mathayomsuksa I Students) Abstract This research intented to study a confirmatory factor analysis of information and communication technology using for learning of mathayomsuksa I students model and empirical data. In this research 719 students were selected by two-stage random sampling from mathayomsuksa I students in educational of service area section thirty first. The instrument which used in collecting data was a questionnaire with five levels of rating scale. For this research, discrimination power of measured instrument were between .55-.83 and reliability was .93. The data were analyzed by Confirmatory Factor Analysis. The research findings were as follows: information and communication technology using for learning of mathayomsuksa I students model was fitted with the empirical data ( <!--?mso-application progid="Word.Document"?--> 14Ï‡2"> =2.92, P value=.087, =2.92, GFI=1.00, AGFI=.98, SRMR=.00, RMSEA=.05). The constructed reliability ( <!--?mso-application progid="Word.Document"?--> 14Ïc"> ) of information and communication technology using for learning model was .90 and average variance extracted ( <!--?mso-application progid="Word.Document"?--> 14Ïv"> ) was .71 respectively. Keywords: information and communication technology using for learning, confirmatory factor analysis